Examining the mediating role of psychological empowerment in the relationship between transformational leadership and employee performance of Sabah public sector / Aminah Ahmad - Ahmad, Aminah (2021)
In this era of globalisation, rapid and ever-changing economic and political landscape, employee performance is the highest priority of management, including the government sector. Employee performance is crucial to the organisation’s success and a pressing issue in the last few decades. Therefore, this study aims to examine the mediating role of psychological empowerment between transformational leadership and employee performance in the public service sector of Sabah. Four hypotheses were tested using a newly developed model based on social exchange theory and transformational leadership. This study employed a quantitative study method using the questionnaire survey instrument. A non-probability sampling technique using the purposive sampling method was applied. The questionnaire was distributed to 380 employees of Support Group 1 & 2, ranging from Grade 19 to Grade 40; 286 questionnaires were successfully collected. Data collected were analysed using SmartPLS Version 3.3.3 and analysed to fulfill the research objectives. The results indicate that transformational leadership has an indirect significant effect on employee performance mediated by psychological empowerment. However, transformational leadership has no direct significant effect on employee performance in Sabah public sector. The findings of this study suggest that psychological empowerment has a significant does mediate the relationship with transformational leadership and employee performance.